2017
DOI: 10.1101/149245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An intron proximal to a PTC enhances NMD inSaccharomyces cerevisiae

Abstract: Nonsense mediated mRNA decay (NMD) denotes that nonsense mutations, or errors in gene expression which introduce a premature translation termination codon (PTC), can lead to a reduction of mRNA level in any organism. Remarkably, whether a PTC will lead to NMD often depends on the presence of a downstream intron, splicing of which marks a spliced mRNA by deposition of the exon junction complex (EJC) in mammalian cells so as to affect its translation and degradation in the cytoplasm. Saccharomyces cerevisiae, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Furthermore, these data re-prompt questioning the fields' communally accepted syllogism that transcripts whose levels are increased in Upf1 depleted cells are therefore likely to be NMD targets. This might not always be a valid explanation: it has previously been argued that only a fraction of these increases might actually be a direct consequence of cytoplasmic mRNA stabilisation (Brogna et al, 2016;Brogna and Wen, 2009;Wen and Brogna, 2010;Wen et al, 2020). Here we have shown that there is overlap between genes associated with Upf1 and genes that have increased mRNA levels in upf1D.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, these data re-prompt questioning the fields' communally accepted syllogism that transcripts whose levels are increased in Upf1 depleted cells are therefore likely to be NMD targets. This might not always be a valid explanation: it has previously been argued that only a fraction of these increases might actually be a direct consequence of cytoplasmic mRNA stabilisation (Brogna et al, 2016;Brogna and Wen, 2009;Wen and Brogna, 2010;Wen et al, 2020). Here we have shown that there is overlap between genes associated with Upf1 and genes that have increased mRNA levels in upf1D.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, EJCs can directly promote activation of NMD, exemplifying how nuclear splicing events communicate with cytoplasmic pathways through RNA-binding proteins for quality control. Interestingly, a recent study in yeast suggested that, despite lacking proteins homologous to EJC core components, an intron in proximity to a PTC enhances NMD [75]. This supports the possibility that a connection between splicing and NMD might be conserved from simple eukaryotic species.…”
Section: Further Surveillance In the Cytoplasm-detection Of Errors Via Nonsense-mediated Decaymentioning
confidence: 78%
“…Therefore, the main function of the EJC in NMD may be to increase the local concentration of such proteins [ 8 ]. The NMD-promoting function of the EJC has been further challenged by the discovery that in Schizosaccharomyces pombe and S. cerevisiae , splicing both upstream and downstream of PTCs enhances NMD, but is independent of EJC components [ 163 , 164 ]. Similarly, according to a recent report, the number of introns determine NMD efficiency in mammalian cells regardless of their position upstream or downstream of a PTC [ 112 ].…”
Section: Are There Any Indispensable Trans -Acmentioning
confidence: 99%